Unconventional resistive switching behavior in ferroelectric tunnel junctions - Mao, H J; Song, C; Xiao, L R; Gao, S; Cui, B; Peng, J J; Li, F; Pan, F (Physical chemistry chemical physics : PCCP, 2015)
We investigate an unconventional resistive switching (RS) behavior in La0.67Sr0.33MnO3/BaTiO3/metal (LSMO/BTO) ferroelectric tunnel junctions (FTJs), which is dominated by the variation of the barrier potential profile modulated by the migration of oxygen vacancies in the p-LSMO/n-BTO junction. The LSMO/BTO/Co junction exhibits a remarkable self-rectifying effect ascribed to the high-density interface state at the BTO/Co interface, in contrast to the symmetric conductivity when the top metal electrode is inert Pt. The effects of ferroelectric polarization on the RS behavior are also emphasized. Our work builds a bridge between FTJs and resistive random access memory devices.